10-Year experience regarding the reliability and morbidity of radio guided lymph node biopsy in penile cancer patients and the associated radiation exposure of medical staff in this procedure. Issue 1 (December 2016) - Lützen, Ulf; Naumann, Carsten; Dischinger, Jens; Marx, Marlies; Baumann, René; Zhao, Yi; Jüptner, Michael; Osmonov, Daniar; Bothe, Katrin; Jünemann, Klaus-Peter; Zuhayra, Maaz
Abstract Background The guidelines of the European Association of Urologists (EAU), of the German Society of Nuclear Medicine (DGN), and the European Society for Medical Oncology (ESMO) recommend sentinel lymph node biopsy (SLNB) for lymph node staging in penile cancer with non-palpable inguinal lymph nodes as one diagnostic method. Despite this, the method is neither widely nor regularly applied in Germany – the same applies to many other countries, which may be due to insecurity in dealing with open radioactive tracers. This study aims to assess the reliability and morbidity of this method, as well as the associated radioactive burden for clinical staff. Methods Between 2006 and 2016, 34 patients with an invasive penile carcinoma and inconspicuous inguinal lymph node status underwent SLNB in 57 groins after application of a radiotracer (Tc-99 m nanocolloid). We collected the results prospectively. The reliability of the method was assessed by determining the false-negative rate. In addition, we evaluated complication rates and determined the radioactive burden for the clinical staff both pre- and intraoperatively. Results SLNB was performed in 34 patients with penile cancer with non-palpable inguinal lymph nodes in 57 groins. In two patients inguinal lymph node metastases were detected by means of SLNB. In one patient recurrent inguinal lymph node disease was found after negative SLNB in both groins. Thus, the false negative rate was 3.13 % per patient (1/32 patients) and 3.51 % per groin (2/57 groins). The morbidity rate was 2.94 % per patient (1/34 patients) and 1.75 % per groin (1/57 groins). Radiation exposure for the clinical staff during this procedure was low at a maximum of ca. four μSV per intervention. Conclusions SLNB is a reliable method with low morbidity that is associated with a low radiation burden for clinical staff. Due to the enhanced methodological and logistic demands, this intervention should be performed in specialized centres and in an interdisciplinary approach.